Negative active material, negative plate and battery

By regulating the relationship between particle size, spherical degree and pore volume of siliceous carbon composite particles, the conductivity and stability problems of silicon-based materials in lithium-ion batteries are solved, and the overall performance of the battery is improved.

CN119324210APending Publication Date: 2025-01-17ZHUHAI COSMX BATTERY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411352896.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-26
Publication Date
2025-01-17

AI Technical Summary

Technical Problem

The existing silicon-based materials have poor ionic conductivity and electronic conductivity and large volume expansion in lithium-ion batteries, resulting in poor first-time Coulomb efficiency, poor rate performance, low temperature performance and cycle stability.

Method used

By controlling the particle size, spherical degree and the relationship between closed and open pore volumes of silicon carbon composite particles, the structure of siliceous carbon composite particles is regulated, and its conductivity and stability are improved to ensure that the capacity is high and the capacity is kept low. volume expansion rate.

Benefits of technology

It achieves a higher ionic conductivity and electronic conductivity in lithium-ion batteries, taking into account the first-time Coulomb efficiency, rate performance, low temperature performance and cycle stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119324210A_ABST
    Figure CN119324210A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of batteries, in particular to a negative active material, a negative plate comprising the negative active material and a battery. The negative electrode active material comprises silicon-carbon composite particles; the particle size Dn10 of the silicon-carbon composite particles is 1-8 [mu] m; the average sphericity degree of the silicon-carbon composite particles is 0.6-1; the silicon-carbon composite particles have closed pores and open pores, and the volume V1 of the closed pores and the volume V2 of the open pores satisfy 0.2 < = V1 / V2 < = 2000. The negative electrode active material disclosed by the invention has relatively high ionic conductivity and electronic conductivity and relatively high structural stability while relatively high gram volume is ensured. Comprising the negative electrode active material disclosed by the invention can give consideration to relatively good initial coulombic efficiency, rate capability, low-temperature performance and cycling stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of batteries, and in particular to a negative electrode active material, a negative electrode sheet comprising the negative electrode active material, and a battery comprising the negative electrode active material. Background Art

[0002] With the rapid development of consumer electronics, electric vehicles, and energy storage power stations, the use of silicon-based materials with higher theoretical lithium storage capacity to replace traditional graphite materials as negative electrode active materials for batteries is an important way to further improve the energy density of lithium-ion batteries. However, existing silicon-based materials not only have poor ionic and electronic conductivity, but also have a large volume expansion rate during the battery charge and discharge cycle, resulting in low initial coulombic efficiency of the manufactured battery, poor rate performance, low temperature performance, and cycle stability. Summary of the invention

[0003] The purpose of the present invention is to overcome the above-mentioned problems existing in silicon-based materials in the prior art, and to provide a negative electrode active material, a negative electrode sheet comprising the negative electrode active material, and a battery comprising the negative electrode active material. The negative electrode active material of the present invention simultaneously controls the particle size, sphericity, and the relationship between the closed pore volume and the open pore volume of the silicon-carbon composite particles, so that the negative electrode active material has good ionic conductivity and electronic conductivity, as well as good structural stability while ensuring a high gram capacity. The battery comprising the negative electrode active material of the present invention can take into account good first coulomb efficiency, rate performance, low temperature performance, and cycle stability.

[0004] In the related art, silicon-based materials have the problems of poor ionic conductivity and electronic conductivity and large volume expansion rate. After extensive research, the inventors of the present invention found that by making silicon and carbon into composite materials and controlling the particle size, sphericity, and relationship between closed pore volume and open pore volume of silicon-carbon composite particles, the negative electrode active material can have good ionic conductivity and electronic conductivity, good structural stability, and small volume expansion rate while ensuring a high gram capacity. The reasons may be:

[0005] First, the pores in the silicon-carbon composite particles include open-pore structures and closed-pore structures, and both open-pore structures and closed-pore structures can play a certain buffering role in the volume expansion of silicon materials. However, there are also major differences between the two. Within a certain range, the larger the volume of the closed pores, the stronger the buffering capacity of the silicon-carbon composite particles for the volume expansion of silicon materials, and the better the structural stability of the silicon-carbon composite particles themselves; but at the same time, it will also lead to a decrease in the gram capacity of the silicon-carbon composite particles. Within a certain range, the larger the volume of the open pores, the larger the contact area between the silicon-carbon composite particles and the electrolyte, which will lead to an increase in side reactions, which is not conducive to the stability of the silicon-carbon composite particles, that is, the stability of the negative electrode active material. In addition, the closed-pore structure is more conducive to the transmission of lithium ions and electrons in the silicon-carbon composite particles than the open-pore structure. Therefore, in order to balance the gram capacity, electronic conductivity, ionic conductivity and stability of the silicon-carbon composite particles, it is necessary to regulate the relationship between the volume of the open pores and the volume of the closed pores.

[0006] Second, the improvement of the performance of silicon-carbon composite particles is limited only by regulating the relationship between the volume of open pores and the volume of closed pores. Therefore, it is necessary to control the average sphericity and particle size of silicon-carbon composite particles at the same time. The average sphericity is an indicator to measure the gap between the particle morphology and the perfect sphere. When the morphology of silicon-carbon composite particles is spherical or nearly spherical, it can evenly disperse the stress when it is squeezed by external force, and it is not easy to deform or crack. In addition, in the process of silicon-carbon composite particles deintercalating lithium, the spherical morphology can help silicon-carbon composite particles react with lithium evenly, disperse the expansion stress when active silicon reacts with lithium, and improve the structural stability of silicon-carbon composite particles. Dn10 is the particle size corresponding to the cumulative number of particles when the particles are arranged from small to large according to the particle size. The appropriate range of Dn10 can make silicon-carbon composite particles have a suitable number of active sites, thereby balancing the conductivity and stability of silicon-carbon composite particles.

[0007] Based on this, the inventors of the present invention proposed the following solution:

[0008] The first aspect of the present invention provides a negative electrode active material, which includes silicon-carbon composite particles; the particle size Dn10 of the silicon-carbon composite particles is 1μm-8μm; the average sphericity of the silicon-carbon composite particles is 0.6-1; the silicon-carbon composite particles have closed pores and open pores, and the volume V1 of the closed pores and the volume V2 of the open pores satisfy 0.2≤V1 / V2≤2000.

[0009] A second aspect of the present invention provides a negative electrode sheet, which comprises the negative electrode active material described in the first aspect of the present invention.

[0010] A third aspect of the present invention provides a battery, the battery comprising the negative electrode active material described in the first aspect of the present invention and / or the negative electrode sheet described in the second aspect of the present invention.

[0011] Through the above technical solution, the present invention has at least the following advantages compared with the prior art:

[0012] (1) The negative electrode active material of the present invention has good ionic conductivity and electronic conductivity while ensuring a high gram capacity;

[0013] (2) The negative electrode active material of the present invention has good structural stability and can maintain low volume expansion during the battery charge and discharge cycle;

[0014] (3) The battery of the present invention can take into account good initial coulombic efficiency, rate performance, low temperature performance and cycle stability.

[0015] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] Figure 1 Shown are schematic diagrams of "open cell" and "closed cell".

[0017] Figure 2 Shown is a transmission electron microscope (TEM) image of silicon-carbon composite particles in an example of the present invention. DETAILED DESCRIPTION

[0018] The specific embodiments of the present invention are described in detail below. It should be understood that the specific embodiments described herein are only used to illustrate and explain the present invention, and are not used to limit the present invention.

[0019] The first aspect of the present invention provides a negative electrode active material, which may include silicon-carbon composite particles. The particle size Dn10 of the silicon-carbon composite particles may be 1 μm-8 μm, for example, 1 μm, 2 μm, 3 μm, 4 μm, 5 μm, 6 μm, 7 μm or 8 μm. The average sphericity of the silicon-carbon composite particles may be 0.6-1, for example, 0.6, 0.65, 0.7, 0.75, 0.8, 0.85, 0.86, 0.87, 0.88, 0.89, 0.9, 0.91, 0.92, 0.93, 0.94, 0.95, 0.96, 0.97, 0.98, 0.99 or 1. The silicon-carbon composite particles may have closed pores and open pores, and the volume V1 of the closed pores and the volume V2 of the open pores satisfy 0.2≤V1 / V2≤2000, for example, 0.2, 1, 5, 10, 20, 30, 40, 50, 60, 70, 80, 90, 100, 200, 300, 400, 500, 600, 700, 800, 900, 1000 or 2000.

[0020] When Dn10 is small (for example, less than 1 μm), the number of small-sized particles in the silicon-carbon composite particles is relatively large. The increase in specific surface area caused by the size effect increases the side reactions between the silicon-carbon composite particles and the electrolyte, which will lead to a decrease in the first coulombic efficiency and volume energy density of the battery. When Dn10 is large (for example, greater than 8 μm), the number of large-sized particles in the silicon-carbon composite particles is relatively large, which will lengthen the migration path of lithium ions in the silicon-carbon composite particles, which not only reduces the conductivity of the silicon-carbon composite particles, but also reduces their capacity, affecting the volume energy density and rate performance of the battery.

[0021] When the average sphericity is 1, it means that the silicon-carbon composite particles have a perfect spherical morphology. When the average sphericity of the silicon-carbon composite particles is too small (for example, less than 0.6), it means that most of the silicon-carbon composite particles deviate from the spherical shape and present an irregular shape. Particles with irregular shapes usually have protruding parts, which are easy to squeeze the separator and the current collector in the battery, thereby aggravating the self-discharge of the battery and deteriorating the storage performance.

[0022] When V1 / V2 is small (for example, less than 0.2), it means that the volume of closed pores is smaller than that of open pores. At this time, the volume expansion of the silicon-carbon composite particles is larger, and the electronic conductivity and ionic conductivity are lower, resulting in lower initial coulombic efficiency and volume energy density of the battery, and a larger cycle volume expansion rate; and when V1 / V2 is large (for example, greater than 2000), it means that the volume of closed pores is larger than that of open pores. At this time, the true density of the silicon-carbon composite particles will be lower, which is not conducive to the volume energy density of the battery.

[0023] In the present invention, the particle size Dn10 of the silicon-carbon composite particles can be tested by conventional methods in the art, such as laser particle size testing method, using a Malvern particle size tester for measurement, and the specific testing steps are as follows: the silicon-carbon composite particles are dispersed in deionized water containing a dispersant (such as nonylphenol polyoxyethylene ether) (the mass content of the dispersant is 0.02%-0.03%), ultrasonicated for 2 minutes, and then placed in a Malvern particle size tester for testing.

[0024] In the present invention, the average sphericity of the silicon-carbon composite particles can be tested by conventional methods in the art, for example, by using image processing software (such as Image Pro Plus), selecting at least 10 silicon-carbon composite particles from a scanning electron microscope (SEM) image of silicon-carbon composite particles at a certain magnification (such as 2500 times), measuring and calculating the circumference and area of ​​each particle, and then calculating the circumference equivalent radius r1 and area equivalent radius r2 of each silicon-carbon composite particle, respectively. The sphericity is r2 / r1, and the average value is taken to obtain the average sphericity of the silicon-carbon composite particles.

[0025] In the present invention, the open pores and the closed pores have the conventional meanings in the art; the open pores generally refer to the pores connected to the outer surface of the silicon-carbon composite particles; the closed pores generally refer to the pores inside the silicon-carbon composite particles that are not connected to the outer surface. Figure 1 The figure shows the schematic diagram of "open pore" and "closed pore". As can be seen from the figure, the silicon-carbon composite particle has 2 closed pores and 1 open pore.

[0026] In the present invention, the volume of the open pores can be measured by conventional methods in the art, such as by gas adsorption. The volume of the closed pores can be calculated by the mass content of elemental silicon, the mass content of elemental carbon and the true density of the silicon-carbon composite particles. The specific calculation formula is as follows: V1 = (1 / c) - 1 / (2.31 × C2 + 2.33 × C3), wherein C2 is the mass content of elemental silicon in the silicon-carbon composite particles, C3 is the mass content of elemental carbon in the silicon-carbon composite particles (C3 can be obtained by scanning electron microscope energy spectrum (SEM-EDS) test), and c is the true density of the silicon-carbon composite particles.

[0027] In one example, 1≤V1 / V2≤400.

[0028] In one example, 2≤V1 / V2≤200.

[0029] In one example, the particle size Dn10 of the silicon-carbon composite particles is 3 μm-6 μm.

[0030] In one example, the average sphericity of the silicon-carbon composite particles is 0.8-1.

[0031] In the present invention, the volume V1 of the closed pores may be 0.001 cm 3 / g-0.4cm 3 / g, for example, 0.001cm 3 / g, 0.005cm 3 / g, 0.01cm 3 / g, 0.05cm 3 / g, 0.1cm 3 / g, 0.2cm 3 / g, 0.3cm 3 / g or 0.4cm 3 / g.

[0032] In one example, the volume V1 of the closed pores is 0.01 cm 3 / g-0.2cm 3 / g.

[0033] In the present invention, the volume V2 of the opening may be 0.0001 cm 3 / g-0.1cm 3 / g, for example, 0.0001cm 3 / g, 0.0005cm 3 / g, 0.001cm 3 / g, 0.005cm 3 / g, 0.01cm 3 / g, 0.05cm 3 / g or 0.1cm 3 / g.

[0034] In one example, the volume V2 of the opening is 0.0005 cm 3 / g-0.05cm 3 / g.

[0035] In the present invention, the silicon-carbon composite particles may include a core-shell structure. Figure 2 The figure shows a transmission electron microscope (TEM) image of a silicon-carbon composite particle in an example of the present invention. It can be seen from the figure that the silicon and carbon in the inner core of the silicon-carbon composite particle are both amorphous, distributed relatively evenly and densely, and have no obvious phase interface; the outer surface of the inner core has a shell with a thickness of about 10nm.

[0036] In the present invention, the core of the core-shell structure may include carbon and silicon, and the shell of the core-shell structure may include carbon.

[0037] In one example, the core includes porous carbon and silicon material located in the pores of the porous carbon.

[0038] In one example, the shell includes amorphous carbon.

[0039] In the present invention, the silicon-carbon composite particles may include oxygen. Doping the silicon-carbon composite particles with oxygen can increase the reaction sites between the silicon-carbon composite particles and lithium ions, thereby improving the lithium ion diffusion coefficient.

[0040] In the present invention, in the silicon-carbon composite particles, the ratio C2 / C1 of the mass content C2 of the silicon element to the mass content C1 of the oxygen element can be 10.5-26500, for example, 10.5, 13.3, 20, 21.6, 30, 40, 50, 60, 70, 80, 90, 100, 200, 300, 400, 500, 600, 650, 700, 800, 900, 1000, 2000, 3000, 4000, 5000, 6000, 7000, 8000, 9000, 10000, 20000 or 26500.

[0041] In one example, C2 / C1 is 13.3-650.

[0042] In one example, C2 / C1 is 21.6-400.

[0043] By controlling C2 / C1, the negative electrode active material can take into account both the gram capacity and ionic conductivity. The doping of oxygen elements can increase the diffusion coefficient of lithium ions in silicon-carbon composite particles, which can not only improve the overall ionic conductivity of the negative electrode active material, but also facilitate the capacity; however, too much oxygen elements will occupy the mass of silicon elements, thereby reducing the gram capacity of the negative electrode active material. Therefore, it is necessary to regulate the content of silicon elements and oxygen elements to meet a specific range. Within this range, the negative electrode active material can take into account both the gram capacity and conductivity, thereby improving the energy density and rate performance of the battery.

[0044] In the present invention, the mass content C2 of silicon element in the silicon-carbon composite particles can be 30%-75%, for example, 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65%, 70% or 75%.

[0045] In one example, C2 is 40%-65%.

[0046] In the present invention, the mass content C1 of oxygen element in the silicon-carbon composite particles can be 20ppm-50000ppm, for example, 20ppm, 30ppm, 40ppm, 50ppm, 60ppm, 70ppm, 80ppm, 90ppm, 100ppm, 200ppm, 300ppm, 400ppm, 500ppm, 600ppm, 700ppm, 800ppm, 900ppm, 1000ppm, 2000ppm, 3000ppm, 4000ppm, 5000ppm, 6000ppm, 7000ppm, 8000ppm, 9000ppm, 10000ppm, 20000ppm, 30000ppm, 40000ppm or 50000ppm.

[0047] In one embodiment, C1 is 1000 ppm-30000 ppm.

[0048] In the present invention, the mass content C2 of silicon and the mass content C1 of oxygen in the silicon-carbon composite particles can be measured by conventional methods in the art, such as by scanning electron microscope energy dispersive spectroscopy (SEM-EDS).

[0049] In the present invention, the silicon-carbon composite particles may further include at least one of potassium, calcium and sodium.

[0050] Doping the silicon-carbon composite particles with at least one of potassium, calcium and sodium can increase the electronic conductivity of the silicon-carbon composite particles and reduce the resistivity of the silicon-carbon composite particles. When the silicon-carbon composite particles are doped with oxygen and at least one of potassium, calcium and sodium, the transmission efficiency of lithium ions and electrons can be improved at the same time, which is more conducive to improving the battery rate performance and low temperature performance.

[0051] In one example, the silicon-carbon composite particles include potassium, calcium, and sodium.

[0052] In the present invention, the sum of the mass contents of potassium, calcium and sodium in the silicon-carbon composite particles may be 30ppm-10000ppm, for example, 30ppm, 40ppm, 50ppm, 60ppm, 70ppm, 80ppm, 90ppm, 100ppm, 200ppm, 300ppm, 400ppm, 500ppm, 600ppm, 700ppm, 800ppm, 900ppm, 1000ppm, 2000ppm, 3000ppm, 4000ppm, 5000ppm, 6000ppm, 7000ppm, 8000ppm, 9000ppm or 10000ppm.

[0053] In one example, the sum of the mass contents of potassium, calcium and sodium in the silicon-carbon composite particles is 100 ppm-500 ppm.

[0054] On the premise that C2 / C1 satisfies a specific relationship, by controlling the sum of the mass contents of potassium, calcium and sodium in the silicon-carbon composite particles, the transmission speed of electrons in the silicon-carbon composite particles can be matched with the transmission speed of ions, which is beneficial to improving the capacity and conductivity of the silicon-carbon composite particles, thereby improving the energy density and rate performance of the battery.

[0055] In the present invention, the mass contents of potassium, calcium and sodium in the silicon-carbon composite particles can be tested by conventional methods in the art, for example, by inductively coupled plasma atomic emission spectroscopy (ICP-AES). The specific testing method is as follows: using the ICP-6800 inductively coupled plasma emission spectrometer of Meixi Instruments, nitric acid and hydrofluoric acid are used to digest the sample during the test, and the standard solution of the corresponding element is used for calibration when testing the content of each element. The test environment temperature is 25°C ± 2°C, the plasma gas flow rate is 15 mL / min, and the injection pump flow rate is 1.5 mL / min.

[0056] In the present invention, in the Raman spectrum of the silicon-carbon composite particles, at 470 cm -1 -480cm -1 It can have the first characteristic peak at 507cm -1 -517cm -1 It may have a second characteristic peak at 1330cm -1 -1350cm -1 It may have a third characteristic peak at 1590cm -1 -1610cm -1 It may have a fourth characteristic peak. The intensity I1 of the first characteristic peak, the intensity I2 of the second characteristic peak, the intensity I3 of the third characteristic peak and the intensity I4 of the fourth characteristic peak satisfy 0.5≤(I1+I3) / (I2+I4)≤3, for example, 0.5, 0.6, 0.65, 0.7, 0.8, 0.9, 1, 1.5, 2, 2.4, 2.5 or 3.

[0057] In one example, 0.65≤(I1+I3) / (I2+I4)≤2.4.

[0058] The intensity I1 of the first characteristic peak can represent the disorder of silicon in the silicon-carbon composite particles, the intensity I2 of the second characteristic peak can represent the order of silicon in the silicon-carbon composite particles, the intensity I3 of the third characteristic peak can represent the disorder of carbon in the silicon-carbon composite particles, and the intensity I4 of the fourth characteristic peak can represent the order of carbon in the silicon-carbon composite particles. The higher the disorder of silicon and carbon in the silicon-carbon composite particles, the more loosely stacked structures of silicon and carbon there are, which is conducive to the transfer of lithium ions from the electrolyte to the interior of the silicon-carbon composite particles and the diffusion of lithium ions in the silicon-carbon composite particles; however, the higher the disorder of silicon and carbon in the silicon-carbon composite particles, the greater the risk of side reactions between the silicon-carbon composite particles and the electrolyte. Therefore, it is necessary to control the relationship between the disorder and order of silicon and carbon in the silicon-carbon composite particles so that the two can be balanced, so that the negative electrode active material can take into account both stability and ionic conductivity. When (I1+I3) / (I2+I4) is too small (for example, less than 0.5), the degree of disorder of silicon and carbon in the silicon-carbon composite particles is lower than the degree of order, which will increase the resistance of lithium ions entering the interior of the silicon-carbon composite particles and is not conducive to the transmission of lithium ions; and when (I1+I3) / (I2+I4) is too large (for example, greater than 3), the degree of disorder of silicon and carbon in the silicon-carbon composite particles is higher than the degree of order, which will lead to an increase in side reactions between the silicon-carbon composite particles and the electrolyte, reduce the gram capacity and stability of the silicon-carbon composite particles, and thus affect the battery's first coulombic efficiency and cycle stability.

[0059] In the present invention, the Raman spectrum of the silicon-carbon composite particles can be obtained by conventional testing methods in the art, such as using a Thermo Fisher Raman spectrometer with a test wave number range of 400 cm -1 -4000cm -1 .

[0060] In the present invention, the XRD diffraction pattern of the silicon-carbon composite particles has a first diffraction peak at 27.4°-29.4° and a second diffraction peak at 42.4°-44.4°. The half-peak width W1 of the first diffraction peak and the half-peak width W2 of the second diffraction peak satisfy 3°≤W1+W2≤35°, for example, 3°, 4°, 5°, 10°, 15°, 20°, 25°, 30° or 35°.

[0061] In one example, 4°≤W1+W2≤20°.

[0062] The first diffraction peak in the XRD diffraction spectrum of the silicon-carbon composite particles corresponds to the characteristic peak of silicon, and the second diffraction peak corresponds to the characteristic peak of carbon. When the half-peak width of the first diffraction peak and the half-peak width of the second diffraction peak satisfy the above relationship, the silicon and carbon in the silicon-carbon composite particles have an appropriate degree of amorphism, which is conducive to the transmission of lithium ions in the silicon-carbon composite particles. When W1+W2 is small (for example, less than 3°), the degree of crystallization of silicon and carbon in the silicon-carbon composite particle body is high, which is not conducive to the rapid deintercalation of lithium ions; and when W1+W2 is large (for example, greater than 35°), the degree of amorphism of silicon and carbon in the silicon-carbon composite particle body is high, and there are many defects in the crystal structure of the particles. These defects will irreversibly consume lithium ions during the first charge and discharge process of the battery, resulting in a low initial coulombic efficiency of the battery.

[0063] In the present invention, the XRD diffraction pattern of the silicon-carbon composite particles can be obtained by conventional testing methods in the art, such as using an X-ray diffraction method and using a Shimadzu XRD-6100 X-ray diffractometer for testing, with a sample weight of 0.5 g / cm 2 The Cu Kα line is used as the incident X-ray, the working voltage of the X-ray source is 40kV, the test power is 2kW, 2θ is used as the horizontal coordinate and the unit is °, the signal intensity is used as the vertical coordinate, the test range is 10°-80°, the scanning rate is 4° / min, and the data point interval is 0.02°.

[0064] In the present invention, the first cycle dQ / dV curve of the button-type half-cell including the silicon-carbon composite particles has a characteristic peak 1 at 0.25V-0.3V and a characteristic peak 2 at 0.4V-0.45V. The ratio of the peak intensity of the characteristic peak 1 to the peak intensity of the characteristic peak 2 can be 1-3, for example, 1, 1.05, 1.5, 2, 2.5 or 3.

[0065] In one example, the ratio of the peak intensity of the characteristic peak 1 to the peak intensity of the characteristic peak 2 is 1.05-2.5.

[0066] During the discharge of button half-cell or charging of lithium-ion battery (full battery), silicon will form lithium-silicon alloy. The characteristic peaks 1 and 2 correspond to Li 15+x Si4 to Li 15 Conversion of Si4 and Li 15 Si4 to Li x The conversion of Si, due to Li 15+x Si4 and Li 15 The structural difference of Si4 is small, while Li 15 Si4 and Li xThe structure of Si is quite different, so the volume change rate of the delithiation process corresponding to characteristic peak 2 is greater. When the peak intensity of characteristic peak 1 and the peak intensity of characteristic peak 2 satisfy the above relationship, it means that the Li generated by the process corresponding to characteristic peak 1 during delithiation of silicon-carbon composite particles is 15 Si4 is quickly converted into Li x Si without accumulating too much Li in the material 15 Si4, therefore the process corresponding to the characteristic peak 2 occurs less frequently, and the volume change rate of the silicon-carbon composite particles is smaller, that is, the silicon-carbon composite particles have better structural stability, and the battery including the negative electrode active material has better cycle capacity retention rate.

[0067] In the present invention, the first-cycle dQ / dV curve of the button-type half-cell including the silicon-carbon composite particles can be tested and obtained by conventional methods in the art. For example, the silicon-carbon composite particles are prepared into a button-type half-cell, the button-type half-cell is discharged to 5mV at 0.05C, and then charged to 1.5V at 0.05C, and "voltage-dQ / dV" is selected in the data processing software of the button-type half-cell (for example, the blue battery test system-data processing software), and the ordinate of the highest point in the 0.25-0.3V and 0.4-0.45V ranges of the dQ / dV curve corresponding to the first-cycle delithiation segment in the figure is taken to represent the intensity of characteristic peak one and characteristic peak two and calculate their ratio.

[0068] Among them, the preparation method of the button half-cell is as follows: silicon-carbon composite particles, 4wt% polyacrylic acid aqueous solution and conductive carbon black are mixed in a mass ratio of 80:10:10 to prepare a slurry, which is coated on the surface of copper foil and dried to obtain a single-sided negative electrode sheet, and then the negative electrode sheet is cut into 12mm small discs with a slicer, and a metal lithium sheet is used as a counter electrode, a 1mol / L lithium hexafluorophosphate-ethylene carbonate / dimethyl carbonate (volume ratio of 1:1) solution is used as an electrolyte, and a Celgard diaphragm is used to assemble a 2016 button half-cell. When testing the dQ / dV curve, charging and discharging are performed in the range of 5mV-1.5V at a current density of 0.1C.

[0069] In the present invention, after the silicon-carbon composite particles are subjected to a pressure of 377 MPa, the change rate of the particle size Dv50 of the silicon-carbon composite particles can be 0-50%, for example, 0, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, 20%, 30%, 40% or 50%.

[0070] In one example, after the silicon-carbon composite particles are subjected to a pressure of 377 MPa, a change rate of a particle size Dv50 of the silicon-carbon composite particles is 0-10%.

[0071] When the change rate of the particle size Dv50 of the silicon-carbon composite particles is within a specific range after being subjected to a pressure of 377 MPa, it indicates that the silicon-carbon composite particles have high mechanical strength and are not easily deformed when subjected to external stress, which is beneficial to improving the battery cycle stability.

[0072] In the present invention, "the rate of change of the particle size Dv50 of the silicon-carbon composite particles after the silicon-carbon composite particles are subjected to a pressure of 377 MPa" refers to the ratio of the difference in particle size Dv50 of the silicon-carbon composite particles before and after being subjected to a pressure of 377 MPa to the particle size Dv50 of the silicon-carbon composite particles before being subjected to a pressure of 377 MPa.

[0073] In the present invention, the specific steps of "the silicon-carbon composite particles are subjected to a pressure of 377 MPa" are as follows: take 1g of silicon-carbon composite particles, use a powder compactor (such as Sansi Zongheng 300kN microcomputer-controlled electronic powder compaction testing machine) to apply a pressure of 377 MPa and maintain it at this pressure for 30 seconds, then release the pressure and take out the powder.

[0074] Dv50 is the particle size corresponding to the cumulative volume distribution of 50% after the particles are arranged from small to large. The particle size Dv50 of the silicon-carbon composite particles can be measured by conventional methods in the art, such as laser particle size measurement, and the specific method is the same as the Dn10 test.

[0075] In the present invention, the true density of the silicon-carbon composite particles can be 1.5 g / cm 3 -2.25g / cm 3 , for example 1.5 g / cm 3 , 1.7g / cm 3 , 1.75g / cm 3 , 2g / cm 3 , 2.15g / cm 3 or 2.25g / cm 3 The appropriate true density range enables the silicon-carbon composite particles to have sufficient closed pore volume to buffer the volume expansion of silicon, so that the battery has a better cycle retention rate and thickness expansion rate.

[0076] In one example, the true density of the silicon-carbon composite particles is 1.7 g / cm 3 -2.15g / cm 3 .

[0077] In the present invention, the true density of the silicon-carbon composite particles can be tested by conventional methods in the art, such as the gas volume displacement method, as follows: use the JW-M100A fully automatic true density tester to test, the test gas is helium, and the test environment temperature is 25°C ± 2°C.

[0078] The present invention also provides a method for preparing the above silicon-carbon composite particles, the method comprising at least the following steps:

[0079] Place the porous carbon material in a vapor deposition device, introduce argon gas, raise the temperature to 400°C-1000°C, keep it warm for 0.5h-12h, and then cool it down to 300°C-500°C; introduce monosilane gas for the first time, and then introduce monosilane gas for the second time; stop introducing monosilane gas, raise the temperature to 500°C-650°C, introduce acetylene gas, and keep it for 0.5h-6h.

[0080] In the present invention, the flow rate of the first introduction is 50 sccm-300 sccm; the time of the first introduction is 1 h-6 h.

[0081] In the present invention, the flow rate of the second introduction is 100 sccm-200 sccm; the time of the first introduction is 1h-3h.

[0082] In the present invention, the flow rate of the introduced acetylene gas is 50 sccm-200 sccm; the time for introducing the acetylene gas is 0.5h-6h.

[0083] In the present invention, the method further comprises pre-treating the porous carbon material and then placing the porous carbon material in the vapor deposition device.

[0084] In the present invention, the pretreatment may include soaking the porous carbon material with a solvent. The solvent may include at least one of potassium hydroxide, sodium hydroxide and calcium hydroxide. The concentration of the solvent is, for example, 0.5 mol / L-2 mol / L. The content of the porous carbon in the solvent may be 0.1 g / 100 mL-5 g / 100 mL. The soaking time may be 1 h-72 h.

[0085] A second aspect of the present invention provides a negative electrode sheet, which comprises the negative electrode active material described in the first aspect of the present invention.

[0086] In the present invention, the negative electrode sheet may include a negative electrode current collector and a negative electrode active material layer located on at least one side surface of the negative electrode current collector.

[0087] In the present invention, the XRD diffraction pattern of the negative electrode active material layer may have a third diffraction peak at 25°-30° and a fourth diffraction peak at 42°-44°. The half-peak width W3 of the third diffraction peak and the half-peak width W4 of the fourth diffraction peak satisfy 0.1°≤W3+W4≤35°, for example, 0.1°, 0.5°, 1°, 2°, 3°, 5°, 10°, 15°, 20°, 25°, 30° or 35°.

[0088] In one example, 0.5°≤W3+W4≤20°.

[0089] In the present invention, the first-cycle dQ / dV curve of the button half-cell including the negative electrode sheet may have a ratio of a maximum value of 0.25V-0.3V to a maximum value of 0.4V-0.45V of 1-15, for example, 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14 or 15.

[0090] In one example, in the first cycle dQ / dV curve of the button-type half-cell including the negative electrode sheet, the ratio of the maximum value at 0.25V-0.3V to the maximum value at 0.4V-0.45V is 1.5-10.

[0091] In the present invention, the negative electrode active material layer may further include a negative electrode conductive agent and a negative electrode binder. The negative electrode conductive agent may include at least one of conductive carbon black, acetylene black, Ketjen black, conductive graphite, carbon nanotubes (including at least one of single-walled carbon nanotubes and multi-walled carbon nanotubes) and carbon fibers. The negative electrode binder may include at least one of polyvinylidene fluoride (PVDF), sodium carboxymethyl cellulose, styrene-butadiene rubber, polytetrafluoroethylene, polyethylene oxide, polyacrylic acid and derivatives thereof.

[0092] In the present invention, the negative electrode active material may further include a carbon-based material. The carbon-based material may include at least one of artificial graphite, natural graphite, mesophase carbon microspheres, soft carbon and hard carbon. The mass ratio of the silicon-carbon composite particles to the carbon-based material may be 1:(0.01-50), for example, 1:0.01, 1:0.05, 1:0.1, 1:0.5, 1:1, 1:5, 1:10, 1:19, 1:20, 1:30, 1:40 or 1:50.

[0093] In one example, the mass ratio of the silicon-carbon composite particles to the carbon-based material is 1:(0.1-19).

[0094] In the present invention, based on the total mass of the negative electrode active material layer, the content of the negative electrode active material can be 80%-99.8% (for example, 80%, 82%, 84%, 86%, 88%, 90%, 92%, 94%, 96%, 98%, 99% or 99.8%), the content of the negative electrode conductor can be 0.1%-10% (for example, 10%, 9%, 8%, 7%, 6%, 5%, 4%, 3%, 2%, 1%, 0.5% or 0.1%), and the content of the negative electrode binder can be 0.1%-10% (for example, 10%, 9%, 8%, 7%, 6%, 5%, 4%, 3%, 2%, 1%, 0.5% or 0.1%).

[0095] The third aspect of the present invention provides a battery, which may include the negative electrode active material described in the first aspect of the present invention and / or the negative electrode sheet described in the second aspect of the present invention.

[0096] In the present invention, the third cycle discharge dQ / dV curve of the battery has a characteristic peak 3 at 3.6V-3.7V and a characteristic peak 4 at 3.8V-4.0V. The ratio of the peak intensity of the characteristic peak 3 to the peak intensity of the characteristic peak 4 can be 1-10, for example, 1, 2, 3, 4, 5, 6, 7, 8, 9 or 10.

[0097] In one example, the ratio of the peak intensity of the characteristic peak three to the peak intensity of the characteristic peak four is 2-6.

[0098] In the present invention, the components of the battery other than the negative electrode sheet (such as the positive electrode sheet, the separator and the electrolyte) can be conventionally selected in the art.

[0099] In one example, the battery further includes a positive electrode sheet. The positive electrode sheet includes a positive electrode active material, and the positive electrode active material includes at least one of lithium cobalt oxide, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, lithium nickel cobalt manganese aluminum oxide, lithium manganese oxide, lithium nickel manganese oxide, lithium nickel oxide, lithium iron phosphate, lithium manganese iron phosphate, lithium vanadium phosphate, and lithium-rich manganese-based materials.

[0100] In one example, the battery comprises a lithium-ion battery.

[0101] In one example, the battery includes a lithium-ion secondary battery.

[0102] It should be noted that the numerical expressions such as "first" and "second" in the present invention are only used to distinguish different substances or usages, and do not represent the difference in order.

[0103] The present invention will be described in detail below by way of examples. The examples described in the present invention are only a part of the examples of the present invention, rather than all of the examples. Based on the examples in the present invention, all other examples obtained by ordinary technicians in the field without creative work are within the scope of protection of the present invention.

[0104] In the following examples, unless otherwise specified, all materials used were commercially available analytical grade.

[0105] The following preparation examples are used to prepare the silicon-carbon composite particles of the present invention.

[0106] Preparation Example 1

[0107] Silicon-carbon composite particles were prepared as follows:

[0108] (1) Pretreatment of porous carbon: The porous carbon material (Dn10 is 5 μm, sphericity is 0.99) is placed in a mixed solution of potassium hydroxide, sodium hydroxide and calcium hydroxide at a ratio of 1 g / 100 mL (the total concentration of potassium hydroxide and sodium hydroxide is 1 mol / L, and the calcium hydroxide solution is a saturated solution) for 12 h, taken out, washed, taken out, washed and dried;

[0109] (2) Place in a vapor deposition furnace, introduce argon gas and raise the temperature to 1000°C for 4 hours, then cool to 500°C, and then introduce monosilane gas with a flow rate of 100 sccm and 200 sccm for 2 hours respectively; then stop introducing monosilane, raise the temperature to 520°C, introduce acetylene gas with a flow rate of 100 sccm, and maintain for 2 hours;

[0110] Among them, the Dn10 of the silicon-carbon composite particles is 5 μm, the average sphericity is 0.99; V1 is about 0.2 cm 3 / g, V2 is about 0.001cm 3 / g, V1 / V2 is 200; C2 is about 53%, C1 is about 21000ppm, C2 / C1 is 25.24; the sum of potassium, calcium and sodium contents is about 300ppm.

[0111] Preparation Example 2

[0112] Silicon-carbon composite particles were prepared as follows:

[0113] (1) Pretreatment of porous carbon: The porous carbon material (Dn10 is 3 μm, sphericity is 0.91) is placed in a mixed solution of potassium hydroxide, sodium hydroxide and calcium hydroxide at a ratio of 1 g / 100 mL (the total concentration of potassium hydroxide and sodium hydroxide is 1 mol / L, and the calcium hydroxide solution is a saturated solution) for 4 h, taken out, washed, taken out, washed and dried;

[0114] (2) Place in a vapor deposition furnace, introduce argon gas and raise the temperature to 1000°C for 2 h, then cool to 500°C, and then introduce monosilane gas with a flow rate of 250 sccm and 150 sccm for 2 h each; then stop introducing monosilane, raise the temperature to 620°C, introduce acetylene gas with a flow rate of 100 sccm, and maintain for 4 h;

[0115] Among them, the Dn10 of the silicon-carbon composite particles is 3 μm, the average sphericity is 0.91; V1 is about 0.01 cm 3 / g, V2 is about 0.0005cm 3 / g, V1 / V2 is 20; C2 is about 65%, C1 is about 30000ppm, C2 / C1 is 21.67; the sum of potassium, calcium and sodium contents is about 100ppm.

[0116] Preparation Example 3

[0117] Silicon-carbon composite particles were prepared as follows:

[0118] (1) Pretreatment of porous carbon: The porous carbon material (Dn10 is 6 μm, sphericity is about 0.8) is placed in a mixed solution of potassium hydroxide, sodium hydroxide and calcium hydroxide at a ratio of 1 g / 100 mL (the total concentration of potassium hydroxide and sodium hydroxide is 1 mol / L, and the calcium hydroxide solution is a saturated solution) for 20 h, taken out, washed, taken out, washed and dried;

[0119] (2) Place in a vapor deposition furnace, introduce argon gas and raise the temperature to 1000°C for 8 hours, then cool to 500°C, and then introduce monosilane gas with a flow rate of 150 sccm and 100 sccm for 2 hours each; then stop introducing monosilane, raise the temperature to 560°C, introduce acetylene gas with a flow rate of 100 sccm, and maintain for 1 hour;

[0120] Among them, the Dn10 of the silicon-carbon composite particles is 6 μm, the average sphericity is 0.8; V1 is about 0.1 cm 3 / g, V2 is about 0.05cm 3 / g, V1 / V2 is 2; C2 is about 40%, C1 is about 1000ppm, C2 / C1 is 400; the sum of potassium, calcium and sodium contents is about 500ppm.

[0121] Preparation Example 4

[0122] Used to verify the impact of changes in "V1 / V2".

[0123] The preparation was carried out in accordance with Preparation Example 2, except that V1 / V2 was adjusted by changing the volume V2 of the opening, as follows:

[0124] In step (2), after the introduction of monosilane was stopped, the temperature was raised to 560° C., and acetylene gas was introduced at a flow rate of 100 sccm and maintained for 1 h;

[0125] Among them, V2 is about 0.05cm 3 / g, V1 / V2 is 0.2; the other parameters are basically the same as those in Preparation Example 2.

[0126] Preparation Example 5

[0127] This group of preparation examples is used to verify the impact of changes in "Dn10".

[0128] This group of preparation examples was carried out with reference to Preparation Example 1, except that the Dn10 of the silicon-carbon composite particles was regulated by changing the Dn10 of the porous carbon material, as follows:

[0129] Preparation Example 5a, the Dn10 of the porous carbon material is 1 μm;

[0130] In Preparation Example 5b, the Dn10 of the porous carbon material is 8 μm.

[0131] Preparation Example 6

[0132] This group of preparation examples is used to verify the impact of changes in "average sphericity".

[0133] This group of preparation examples was carried out with reference to Preparation Example 1, except that the average sphericity of the silicon-carbon composite particles was regulated by changing the average sphericity of the porous carbon material, as follows:

[0134] Preparation Example 6a, the average sphericity of the porous carbon material is 0.71;

[0135] In Preparation Example 6b, the average sphericity of the porous carbon material is 0.6.

[0136] Preparation Example 7

[0137] This group of preparation examples is used to verify the impact of changes in the "volume V1 of closed pores".

[0138] This group of preparation examples was carried out with reference to Preparation Example 1, except that V1 was regulated by changing the flow rate and time of monosilane, as follows:

[0139] Preparation Example 7a, in step (2), after the temperature dropped to 500° C., monosilane gas was introduced at a flow rate of 50 sccm for 6 h, and then monosilane gas was introduced at a flow rate of 200 sccm for 3 h;

[0140] Among them, V1 is about 0.001cm 3 / g, V1 / V2 is 1; C2 is about 75%, C2 / C1 is 37.5;

[0141] Preparation Example 7b, in step (2), after the temperature dropped to 500° C., monosilane gas was introduced at a flow rate of 300 sccm for 1 h, and then monosilane gas was introduced at a flow rate of 100 sccm for 1 h;

[0142] Among them, V1 is about 0.4cm 3 / g, V1 / V2 is 400; C2 is about 30%, C2 / C1 is 15.

[0143] Preparation Example 8

[0144] This group of preparation examples is used to verify the impact of changes in the "opening volume V2".

[0145] This group of preparation examples was carried out with reference to Preparation Example 1, except that V2 was regulated by changing the holding time of the acetylene gas, as follows:

[0146] Preparation Example 8a, in step (2), acetylene gas was introduced at a flow rate of 100 sccm and maintained for 6 hours;

[0147] Among them, V2 is about 0.0001cm 3 / g, V1 / V2 is 2000;

[0148] Preparation Example 8b, in step (2), acetylene gas was introduced at a flow rate of 100 sccm and maintained for 0.5 h;

[0149] Among them, V2 is about 0.1cm 3 / g, V1 / V2 is 2.

[0150] Preparation Example 9

[0151] Used to verify the impact of changes in the "core-shell structure".

[0152] In step (2), after the introduction of monosilane is stopped, acetylene gas is not introduced, thereby obtaining silicon-carbon composite particles (without a shell).

[0153] Preparation Example 10

[0154] This group of preparation examples is used to verify the impact of the change of "C2 / C1".

[0155] This group of preparation examples were carried out with reference to Preparation Example 2 and Preparation Example 3, except that the C2 / C1 was controlled by changing the holding time of the porous carbon with argon gas introduced and the temperature raised to 1000°C, as follows:

[0156] Preparation Example 10a was prepared by referring to Preparation Example 2. In step (2), the porous carbon was placed in a vapor deposition furnace, argon gas was introduced, and the temperature was raised to 1000° C. and kept for 8 h, and then the temperature was lowered to 500° C.;

[0157] Among them, C2 is about 65%, C1 is about 1000ppm, and C2 / C1 is 650;

[0158] Preparation Example 10b was prepared by referring to Preparation Example 3. In step (2), the porous carbon was placed in a vapor deposition furnace, argon gas was introduced, and the temperature was raised to 1000° C. and kept for 0.5 h, and then the temperature was lowered to 500° C.;

[0159] Among them, C2 is about 40%, C1 is about 30000ppm, and C2 / C1 is 13.33.

[0160] Preparation Example 11

[0161] This group of preparation examples is used to verify the impact of changes in the "mass content of oxygen element C1".

[0162] This group of preparation examples was carried out with reference to Preparation Example 1, except that C1 was regulated by changing the temperature and / or insulation time of the porous carbon passing argon gas, as follows:

[0163] Preparation Example 11a, in step (2), argon gas was introduced and the temperature was raised to 1000° C. and maintained for 12 h;

[0164] Among them, C2 is about 53%, C1 is about 20ppm, and C2 / C1 is 26500;

[0165] Preparation Example 11b, in step (2), argon gas was introduced and the temperature was raised to 400° C. and maintained for 8 h;

[0166] Among them, C2 is about 53%, C1 is about 50000ppm, and C2 / C1 is 10.6.

[0167] Preparation Example 12

[0168] This group of preparation examples is used to verify the effects of changes in "potassium, calcium and sodium elements".

[0169] This group of preparation examples was carried out with reference to Preparation Example 1, except that the potassium element, calcium element and sodium element were changed by changing the pretreatment conditions of the porous carbon, as follows:

[0170] Preparation Example 12a, replacing the mixed solution of potassium hydroxide, sodium hydroxide and calcium hydroxide in step (1) with a saturated solution of calcium hydroxide), the soaking time is 15 hours; wherein the content of calcium element is about 300 ppm;

[0171] In Preparation Example 12b, the pretreatment of porous carbon in step (1) was not performed.

[0172] Preparation Example 13

[0173] This group of preparation examples is used to verify the impact of changes in the "sum of potassium, calcium and sodium content".

[0174] This group of preparation examples was carried out with reference to Preparation Example 1, except that the sum of the contents of potassium, calcium and sodium was regulated by changing the pretreatment time of the porous carbon, as follows:

[0175] Preparation Example 13a, in step (1), the porous carbon is immersed in the mixed solution for 1 hour;

[0176] Among them, the sum of potassium, calcium and sodium contents is about 30ppm;

[0177] Preparation Example 13b, in step (1), the porous carbon is immersed in the mixed solution for 72 hours;

[0178] Among them, the sum of the contents of potassium, calcium and sodium is about 10,000 ppm.

[0179] The shell of the silicon-carbon composite particles prepared in the above preparation example includes amorphous carbon.

[0180] Comparative Preparation Example 1

[0181] The preparation was carried out in accordance with Preparation Example 1, except that the Dn10 of the porous carbon material used was 0.5 μm and the average sphericity was 0.99, and the Dn10 of the prepared silicon-carbon composite particles was 0.5 μm and the average sphericity was 0.99.

[0182] Comparative Preparation Example 2

[0183] The preparation was carried out in accordance with Preparation Example 1, except that the porous carbon material used had a Dn10 of 10 μm and an average sphericity of 0.99, and the prepared silicon-carbon composite particles had a Dn10 of 10 μm and an average sphericity of 0.99.

[0184] Comparative Preparation Example 3

[0185] The preparation was carried out in accordance with Preparation Example 1, except that the Dn10 of the porous carbon material used was 5 μm and the average sphericity was 0.5, and the Dn10 of the prepared silicon-carbon composite particles was 5 μm and the average sphericity was 0.5.

[0186] Comparative Preparation Example 4

[0187] The method was carried out in accordance with Preparation Example 1, except that in step (2), after the temperature dropped to 500°C, monosilane gas was first introduced at a flow rate of 50 sccm for 6 h, and then monosilane gas was introduced at a flow rate of 200 sccm for 1 h, and then the introduction of monosilane was stopped, the temperature was raised to 520°C, and acetylene gas was introduced at a flow rate of 100 sccm and maintained for 0.5 h; wherein V1 was approximately 0.001 cm 3 / g, V2 is about 0.1cm 3 / g, V1 / V2 is 0.01, and C2 is about 75%.

[0188] Comparative Preparation Example 5

[0189] The method was carried out in accordance with Preparation Example 1, except that in step (2), after the temperature dropped to 500°C, monosilane gas was first introduced at a flow rate of 300 sccm for 1 h, and then monosilane gas was introduced at a flow rate of 100 sccm for 1 h, and then the introduction of monosilane was stopped, the temperature was raised to 520°C, and acetylene gas was introduced at a flow rate of 100 sccm for 6 h; wherein V1 was approximately 0.4 cm 3 / g, V2 is about 0.0001cm 3 / g, V1 / V2 is 4000, and C2 is about 30%.

[0190] Test Case I

[0191] (1) Raman spectroscopy test

[0192] The silicon-carbon composite particles prepared in Preparation Examples 1-3 were subjected to Raman spectroscopy testing, and the results are recorded in Table 1. The results of the remaining preparation examples all satisfied 0.65≤(I1+I3) / (I2+I4)≤2.4.

[0193] (2) XRD test

[0194] The silicon-carbon composite particles prepared in Preparation Examples 1-3 were subjected to XRD testing, and the results are recorded in Table 1. The results of the remaining preparation examples all satisfied 4°≤W1+W2≤20°.

[0195] (3) dQ / dV curve

[0196] The button half-cells prepared with the silicon-carbon composite particles obtained in Preparation Examples 1-3 were subjected to the first cycle dQ / dV curve test, and the results are recorded in Table 1. The results of the remaining preparation examples all satisfied that the ratio of the peak intensity of characteristic peak one to the peak intensity of characteristic peak two was 1.05-2.5.

[0197] (4) Stress test

[0198] The silicon-carbon composite particles prepared in the preparation examples were subjected to a 377MPa pressure test. The results showed that, except for the group of Preparation Example 6, the particle size Dv50 change rate of all the silicon-carbon composite particles prepared in the preparation examples was 0-10%; and the particle size Dv50 change rate in the group of Preparation Example 6 was 0-50%.

[0199] (5) True density test

[0200] The silicon-carbon composite particles prepared in the preparation examples were tested for true density. The results showed that the true density of the silicon-carbon composite particles prepared in all the preparation examples was 1.5 g / cm 3 -2.25g / cm 3 The true density of the silicon-carbon composite particles prepared in Preparation Examples 1-3 was 1.7 g / cm 3 , 2.15g / cm 3 and 1.95g / cm 3 .

[0201] Table 1

[0202] <![CDATA[(I1+I3) / (I2+I4)]]> <![CDATA[W1+W2]]> The peak intensity ratio of characteristic peak 1 to characteristic peak 2 Preparation Example 1 1.143 10° 1.6 Preparation Example 2 2.40 4° 1.06 Preparation Example 3 0.657 20° 2.5

[0203] The following examples are provided to illustrate the batteries of the present invention.

[0204] Example 1

[0205] Prepare as follows:

[0206] (1) Preparation of negative electrode sheet

[0207] Artificial graphite, the silicon-carbon composite particles prepared in Preparation Example 1, sodium carboxymethyl cellulose, styrene-butadiene rubber and Super P were mixed in a mass ratio of 87.7:8.8:1.6:1.6:0.3, deionized water was added, and a negative electrode slurry was obtained under the action of a vacuum mixer; the negative electrode slurry was evenly coated on both sides of the copper foil, placed in an oven at 80°C and dried for 12 hours, and a negative electrode sheet was obtained after rolling and slitting.

[0208] (2) Preparation of positive electrode

[0209] Lithium cobalt oxide, polyvinylidene fluoride, acetylene black and carbon nanotubes are mixed in a mass ratio of 96:2:1.5:0.5, N-methylpyrrolidone is added, and stirred under the action of a vacuum mixer until a uniform positive electrode slurry is mixed; the positive electrode slurry is evenly coated on the surfaces of both sides of the aluminum foil, placed in an oven for baking, and then transferred to a 120°C oven for drying for 8 hours, and the positive electrode sheets are obtained after rolling and slitting.

[0210] (3) Preparation of lithium-ion batteries

[0211] The negative electrode sheet prepared in step (1), the separator (a polyethylene film with a thickness of 8 μm) and the positive electrode sheet prepared in step (2) are stacked in order, ensuring that the separator is located between the positive and negative electrode sheets to play an isolating role, and then a bare battery cell is obtained by winding; the bare battery cell is placed in an aluminum-plastic film shell, and an electrolyte (a mixed solution of lithium hexafluorophosphate dissolved in ethylene carbonate / dimethyl carbonate (volume ratio 1:1) and 5 vol.% fluoroethylene carbonate, wherein the concentration of lithium hexafluorophosphate is 1 mol / L) is injected into the dried bare battery cell, and a lithium ion battery is obtained through vacuum packaging, standing, forming, shaping, sorting and other processes.

[0212] (4) Preparation of button-type half-cell

[0213] The silicon-carbon composite particles prepared in Preparation Example 1, Super P, sodium carboxymethyl cellulose and styrene-butadiene rubber were mixed in a mass ratio of 96.5:1.6:1.6:0.3, deionized water was added, and the mixture was mixed evenly under the action of a vacuum mixer to obtain a buckle-type negative electrode slurry; the buckle-type negative electrode slurry was coated on a copper foil, dried in an oven at 80°C, and then dried in a vacuum oven at 100°C for 12 hours to obtain a surface density of about 3 mg / cm 2anode sheet; in a dry environment, the anode sheet was punched into anode discs with a diameter of 12 mm using a punching machine; in a glove box, the anode disc was used as a working electrode, the metal lithium sheet was used as a counter electrode, a polyethylene diaphragm with a thickness of 20 μm was used as an isolation membrane, and an electrolyte (a mixed solution of lithium hexafluorophosphate dissolved in ethylene carbonate / dimethyl carbonate (volume ratio 1:1) and 5 vol.% fluoroethylene carbonate, in which the concentration of lithium hexafluorophosphate was 1 mol / L) was added to assemble a button half-cell.

[0214] The groups of Examples 2 to 13 and Comparative Examples 1 to 5 were carried out with reference to Example 1, except that the silicon-carbon composite particles were prepared by replacing Preparation Example 1, as shown in Table 2 for details.

[0215] Example 14 Group

[0216] This group of examples is used to verify the impact of changes in the "mass ratio of silicon-carbon composite particles to carbon-based materials".

[0217] This group of examples is carried out with reference to Example 1, except that the mass ratio of the silicon-carbon composite particles and the artificial graphite is changed, as follows:

[0218] Example 14a, artificial graphite, the silicon-carbon composite particles prepared in Preparation Example 1, sodium carboxymethyl cellulose, styrene-butadiene rubber and Super P were mixed in a mass ratio of 8.8:87.7:1.6:1.6:0.3;

[0219] Example 14b, artificial graphite, the silicon-carbon composite particles prepared in Preparation Example 1, sodium carboxymethyl cellulose, styrene-butadiene rubber and Super P were mixed in a mass ratio of 91.7:4.8:1.6:1.6:0.3;

[0220] In Example 14c, artificial graphite, the silicon-carbon composite particles prepared in Preparation Example 1, sodium carboxymethyl cellulose, styrene-butadiene rubber and Super P were mixed in a mass ratio of 94.6:1.9:1.6:1.6:0.3;

[0221] In Example 14d, the silicon-carbon composite particles prepared in Preparation Example 1, sodium carboxymethyl cellulose, styrene-butadiene rubber and Super P were mixed in a mass ratio of 96.5:1.6:1.6:0.3.

[0222] Test Case II

[0223] (1) XRD test of negative electrode active material layer

[0224] The negative electrode active material layers prepared in Examples 1-14 were subjected to XRD testing, and the results were as follows: W3+W4 in Example 1 was 0.5°, W3+W4 in Example 2 was 20°, W3+W4 in Example 3 was 10.1°, and the remaining Examples all satisfied 0.5°≤W3+W4≤20°.

[0225] (2) dQ / dV curve

[0226] The negative electrode sheets prepared in Examples 1-14 were made into button-type half-cells for the first-cycle dQ / dV curve test, and the results were as follows: in Example 1, the ratio of the maximum value at 0.25V-0.3V to the maximum value at 0.4V-0.45V was 1.6, in Example 2 it was 10, in Example 3 it was 1.53, and the remaining Examples all satisfied the ratio of the maximum value at 0.25V-0.3V to the maximum value at 0.4V-0.45V of 1.5-10.

[0227] The batteries prepared in Examples 1-14 were subjected to dQ / dV testing, and the results of the third cycle discharge dQ / dV curves of the batteries were as follows: the ratio of the peak intensity of characteristic peak one to characteristic peak two in Example 1 was 2, Example 14a was 2, Example 14b was 6, Example 14c was 10, Example 14d was 1, and the remaining examples all met 1-10.

[0228] (3) Cycle test

[0229] The lithium ion batteries prepared in the examples and comparative examples were subjected to cycle tests, and the specific test methods are as follows:

[0230] The battery was charged to 4.5V at a current density of 2C, then charged at a constant voltage of 4.5V with a cut-off current of 0.05C, and then left to stand for 10 minutes. The thickness of the battery at this time was recorded as the initial thickness; then discharged to 3.0V at a current density of 1.5C, and then left to stand for 10 minutes. The discharge capacity of the battery at this time was recorded as the initial capacity; the above charging and discharging process was repeated until the 500th cycle of the constant voltage charging process was completed and left to stand for 10 minutes. The thickness of the battery was tested and recorded as the thickness after the cycle, and then discharged to 3.0V at a current density of 1.5C, and left to stand for 10 minutes. The discharge capacity of the battery at this time was recorded as the capacity after the cycle. Then the cycle capacity retention rate = capacity after the cycle × 100% / initial capacity, thickness expansion rate = (thickness after the cycle - initial thickness) × 100% / initial thickness, and the cycle capacity retention rate and thickness expansion rate were recorded in Table 2.

[0231] (4) Energy density test

[0232] The lithium ion batteries prepared in the examples and comparative examples were subjected to energy density tests, and the specific test methods are as follows:

[0233] The battery was charged to 4.5V at a current density of 0.2C, then charged at a constant voltage of 4.5V with a cut-off current of 0.02C. After standing for 10 minutes, it was discharged to 3.0V at a current density of 0.2C and stood for 10 minutes. The first-cycle discharge capacity and first-cycle discharge energy of the battery were recorded. The battery was then charged at a current density of 0.2C with a cut-off condition that the charging capacity reached half of the first-cycle discharge capacity. After the cut-off, the battery was removed and the thickness, length and width of the battery were measured. The energy density of the battery = first-cycle discharge energy / (length × width × thickness). The results are recorded in Table 2.

[0234] (5) First Coulomb efficiency test

[0235] The button-type half-cells prepared in Examples 1-13 and Comparative Examples were subjected to the first coulombic efficiency test, and the specific test method is as follows:

[0236] After the battery was left to stand for 2 hours, it was discharged at a constant current density of 0.1C to 5mV. After standing for 10 minutes, it was discharged again at a current density of 0.01C to 5mV. After standing for another 10 minutes, it was charged at a constant current density of 0.05C to 1.5V. The first coulomb efficiency = charging capacity × 100% / discharge capacity. The results are recorded in Table 2.

[0237] (6) Rate performance test

[0238] The lithium ion batteries prepared in the examples and comparative examples were subjected to rate discharge capacity tests, and the specific test methods are as follows:

[0239] The battery was charged to 4.5V at a current density of 0.2C, then charged at a constant voltage of 4.5V with a cut-off current of 0.02C. After standing for 10 minutes, it was discharged to 3.0V at current densities of 0.2C and 1C respectively. The ratio of the capacity discharged at 1C to the capacity discharged at 0.2C is the rate discharge capability of the battery. The results are recorded in Table 3.

[0240] (7) Self-discharge test

[0241] The lithium ion batteries prepared in the examples and comparative examples were subjected to self-discharge tests, and the specific test methods are as follows:

[0242] The battery was charged at a constant current density of 0.2C to 4.5V, and then charged at a constant voltage of 4.5V with a cut-off current of 0.02C. After standing for 10 minutes, the open circuit voltage V1 of the battery was recorded. Then, the battery was kept standing for 24 hours, and the open circuit voltage V2 of the battery was recorded after the standing was completed. The self-discharge degree of the battery is k=(V1-V2) / 24 (in mV / h). The results are recorded in Table 3.

[0243] (8) Storage performance test

[0244] The lithium ion batteries prepared in the examples and comparative examples were tested for storage performance, and the specific testing method is as follows:

[0245] The battery was charged to 4.5V at a current density of 0.2C, then charged at a constant voltage of 4.5V with a cutoff current of 0.02C. After standing for 10 minutes, it was discharged to 3.0V at a current density of 0.2C and stood for 10 minutes, and the first-cycle discharge capacity of the battery was recorded; the battery was then charged at a current density of 0.2C with a constant current, and the cutoff condition was that the charging capacity reached half of the first-cycle discharge capacity. After the cutoff, the battery was removed and the thickness of the battery was measured, which was recorded as the thickness before storage; the battery was then charged to 4.5V at a current density of 0.2C, then charged at a constant voltage of 4.5V with a cutoff current of 0.02C, and then placed in a 60°C blast oven for 35 days. At the end of the placement, its thickness was tested and recorded as the thickness after storage. The thickness expansion rate of the battery after storage at 60°C for 35 days = (thickness after storage - thickness before storage) / thickness before storage. The results are recorded in Table 3.

[0246] (9) Low temperature performance test

[0247] The lithium ion batteries prepared in the examples and comparative examples were subjected to low temperature performance tests, and the specific test methods are as follows:

[0248] The battery was charged to 4.5V at a current density of 0.2C, then charged at a constant voltage of 4.5V with a cut-off current of 0.02C. After standing for 10 minutes, it was discharged to 3.0V at a current density of 0.2C at ambient temperatures of 25°C and -20°C, respectively. The ratio of the capacity discharged at -20°C to the capacity discharged at 25°C is the low-temperature discharge capability of the battery. The results are recorded in Table 3.

[0249] (10) Ion diffusion coefficient test

[0250] The button-type half-cells prepared in Examples 1-13 and the comparative example were tested for ion diffusion coefficients. The specific test method is as follows:

[0251] After the button half-cell was left to stand for 2 hours, it was discharged at a constant current density of 0.1C to 5mV and left to stand for 10 minutes; then it was discharged at a current density of 0.01C to 5mV and left to stand for 10 minutes again; then it was charged at a current density of 0.05C to 1.5V and left to stand for 10 minutes again, and the process of discharging at a constant current density of 0.1C for 30 minutes and leaving to stand for 30 minutes was repeated until the battery voltage was lower than 0.1V. After leaving to stand for 30 minutes again, the voltage E1 at this time was recorded, and then it was discharged at a constant current density of 0.1C for 30 minutes, and the voltage E2 at the time of discharge 10s and the voltage E3 at the end of discharge were recorded, and then it was left to stand for 60 minutes, and the voltage E4 after leaving to stand for 60 minutes was recorded. According to the formula

[0252]

[0253] The silicon-carbon composite particles can be obtained at 0.1V (vs Li + The lithium ion diffusion coefficient (in cm) at the potential of 2 / s), where τ is the relaxation time, i.e., τ = 3600s; n is the molar number of silicon-carbon composite particles, V is the molar volume of silicon-carbon composite particles, and n×V is the volume of silicon-carbon composite particles used in the test, which can be calculated based on the mass w of the coating in the button-type half-cell negative electrode sheet and the true density ρ of the silicon-carbon composite particles, n×V = 0.965×w / ρ; S is the geometric area of ​​the button-type half-cell negative electrode sheet, i.e., S = 1.13cm 2 , and record the results in Table 3.

[0254] Table 2

[0255]

[0256]

[0257] Table 3

[0258]

[0259]

[0260] Note: Since the first coulombic efficiency and lithium ion diffusion coefficient were tested by button half-cells, the button half-cells of Example 14 were the same as those of Example 1, so the first coulombic efficiency and lithium ion diffusion coefficient tests were not performed on Example 14. The “ / ” in Tables 2 and 3 indicates that they were not tested.

[0261] It can be seen from Table 2 and Table 3 that the battery prepared by the negative electrode active material of the present invention can take into account better first coulombic efficiency, rate performance, low temperature performance and cycle stability compared with the comparative example.

[0262] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. A negative electrode active material, characterized in that: The negative electrode active material includes silicon-carbon composite particles; the particle size Dn10 of the silicon-carbon composite particles is 1 μm-8 μm; the average sphericity of the silicon-carbon composite particles is 0.6-1; the silicon-carbon composite particles have closed pores and open pores, and the volume V1 of the closed pores and the volume V2 of the open pores satisfy 0.2≤V1 / V2≤2000.

2. The negative electrode active material according to claim 1, wherein 1≤V1 / V2≤400; preferably, 2≤V1 / V2≤200; And / or, the particle size Dn10 of the silicon-carbon composite particles is 3 μm-6 μm; and / or, the average sphericity of the silicon-carbon composite particles is 0.8-1; And / or, the volume V1 of the closed pore is 0.001cm 3 / g-0.4cm 3 / g; preferably 0.01cm 3 / g-0.2cm 3 / g; And / or, the volume V2 of the opening is 0.0001cm 3 / g-0.1cm 3 / g; preferably 0.0005cm 3 / g-0.05cm 3 / g.

3. The negative electrode active material according to claim 1 or 2, wherein The silicon-carbon composite particles include a core-shell structure; the core of the core-shell structure includes carbon and silicon, and the shell of the core-shell structure includes carbon; Preferably, the core comprises porous carbon and silicon material located in the pores of the porous carbon; Preferably, the shell comprises amorphous carbon.

4. The negative electrode active material according to claim 1 or 2, wherein The silicon-carbon composite particles include oxygen element; Preferably, in the silicon-carbon composite particles, the ratio C2 / C1 of the silicon content C2 to the oxygen content C1 is 10.5-26500; more preferably 21.6-400.

5. The negative electrode active material according to claim 4, wherein C2 is 30%-75%; preferably 40%-65%; And / or, C1 is 20ppm-50000ppm; preferably 1000ppm-30000ppm.

6. The negative electrode active material according to claim 1 or 2, wherein: The silicon-carbon composite particles include at least one of potassium, calcium and sodium; Preferably, the silicon-carbon composite particles include potassium, calcium and sodium; More preferably, the sum of the mass contents of potassium, calcium and sodium in the silicon-carbon composite particles is 30 ppm-10000 ppm; preferably 100 ppm-500 ppm.

7. The negative electrode active material according to claim 1 or 2, wherein: In the Raman spectrum of the silicon-carbon composite particles, at 470 cm -1 -480cm -1 The first characteristic peak is at 507cm -1 -517cm -1 There is a second characteristic peak at 1330cm -1 -1350cm -1 It has a third characteristic peak at 1590cm -1 -1610cm -1 having a fourth characteristic peak; the intensity I1 of the first characteristic peak, the intensity I2 of the second characteristic peak, the intensity I3 of the third characteristic peak and the intensity I4 of the fourth characteristic peak satisfy 0.5≤(I1+I3) / (I2+I4)≤3; preferably, 0.65≤(I1+I3) / (I2+I4)≤2.4; And / or, the XRD diffraction pattern of the silicon-carbon composite particles has a first diffraction peak at 27.4°-29.4° and a second diffraction peak at 42.4°-44.4°; the half-peak width W1 of the first diffraction peak and the half-peak width W2 of the second diffraction peak satisfy 3°≤W1+W2≤35°; preferably, 4°≤W1+W2≤20°; And / or, the first cycle dQ / dV curve of the button half-cell including the negative electrode active material has a characteristic peak 1 at 0.25V-0.3V and a characteristic peak 2 at 0.4V-0.45V; the ratio of the peak intensity of the characteristic peak 1 to the peak intensity of the characteristic peak 2 is 1-3; preferably 1.05-2.5; And / or, after the silicon-carbon composite particles are subjected to roller pressing at 377 MPa, the change rate of the particle size Dv50 of the silicon-carbon composite particles is 0-50%, preferably 0-10%.

8. A negative electrode sheet, characterized in that: The negative electrode sheet comprises the negative electrode active material according to any one of claims 1 to 7.

9. The negative electrode sheet according to claim 8, wherein: The negative electrode sheet comprises a negative electrode current collector and a negative electrode active material layer located on at least one side of the negative electrode current collector; the negative electrode active material layer comprises the negative electrode active material; The XRD diffraction spectrum of the negative electrode active material layer has a third diffraction peak at 25°-30° and a fourth diffraction peak at 42°-44°; the half-peak width W3 of the third diffraction peak and the half-peak width W4 of the fourth diffraction peak satisfy 0.1°≤W3+W4≤35°; preferably, 0.5°≤W3+W4≤20°; And / or, the first-cycle dQ / dV curve of the button-type half-cell including the negative electrode sheet has a ratio of a maximum value at 0.25V-0.3V to a maximum value at 0.4V-0.45V of 1-15; preferably 1.5-10.

10. A battery, characterized in that: The battery comprises the negative electrode active material according to any one of claims 1 to 7 and / or the negative electrode sheet according to claim 8 or 9.

11. The battery according to claim 10, wherein The third cycle discharge dQ / dV curve of the battery has a characteristic peak three at 3.6V-3.7V and a characteristic peak four at 3.8V-4.0V; the ratio of the peak intensity of the characteristic peak three to the peak intensity of the characteristic peak four is 1-10, preferably 2-6.